(untitled) (مجلة الواحات للبحوث والدراسات, 2020)
The Term Represents The Key To Any Scholarly Subject, And If Narratives Find Their Way In The Field Of Modern Literary Criticism In General, And In The Analysis Of Narrative Texts In Particular, In The Field Of Contemporary Arab Critical Studies, Its Terminology Is Still Controversial Among Scholars And Specialists: How To Deal With The West The Following Terms (Narrative, Narrative Science, Narratives, Narrative), How The Arabs Received These Terms And Their Concepts, And To What Extent Have Arab Critics Been Successful In Dealing With These Incoming Terms? We Have Identified The Causes Of This Phenomenon, Which Has Become A Major Concern In Modern Literary Criticism, Suggesting Some Of The Solutions That We Think May Contribute To The Solution Of Some Of The Problems Of The Narrative Term. Key Words: Term , Money ,Listing ,Chaos ,Multiple.